Implementation of Project-Based Learning and Cooperative Learning Models of the ASSURE Type to Improve Students' Problem-Solving Skills and Learning Outcomes - Sri Suci Lestari (Yayasan Arfah Bin Haji Muhammad Saleh, 2026)
Improving the quality of learning at various levels of education requires the implementation of models capable of developing higher-order thinking skills while improving learning outcomes. Project-Based Learning (PjBL) has proven effective in improving problem-solving skills in high school students, particularly in Physics learning on rectilinear motion. On the other hand, the ASSURE cooperative learning model has successfully improved elementary school students' learning outcomes through the stages of learning needs analysis, goal setting, strategy selection, active participation, and ongoing evaluation. This article aims to examine the potential of integrating PjBL and ASSURE as a comprehensive approach across educational levels to improve problem-solving skills and student learning outcomes. The methods used are literature review and synthesis of previous research results. The results of the study indicate that the PjBL–ASSURE integration is complementary: PjBL strengthens investigative activities and product creation, while ASSURE strengthens learning planning, media differentiation, and ongoing evaluation. The integration of the two has the potential to produce meaningful, adaptive, and contextual learning. Further research is recommended to empirically test this integrative model across various subjects and educational levels.